2018
DOI: 10.1007/s00402-018-3025-7
|View full text |Cite
|
Sign up to set email alerts
|

Graft tears after arthroscopic superior capsule reconstruction (ASCR): pattern of failure and its correlation with clinical outcome

Abstract: IV, case series, treatment study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
209
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(219 citation statements)
references
References 45 publications
9
209
0
1
Order By: Relevance
“…On including only the cases of Hamada classifications 1-3, retear rate was 7.7% (2 cases). In addition, in our study, neither SSP, ISP nor SubS showed any statistically significant progress or improvement in fatty degeneration preoperatively and postoperatively (Table 2) and these findings were similar to those reported by Mihata et al [20] and Lim et al [24] Moreover, in the grading of preoperative Goutallier scores, no significant differences were observed between the retear and no-retear groups (Table 4). When fatty degeneration is observed on MRI, muscle flexibility and cuff mobility are often reduced preoperatively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On including only the cases of Hamada classifications 1-3, retear rate was 7.7% (2 cases). In addition, in our study, neither SSP, ISP nor SubS showed any statistically significant progress or improvement in fatty degeneration preoperatively and postoperatively (Table 2) and these findings were similar to those reported by Mihata et al [20] and Lim et al [24] Moreover, in the grading of preoperative Goutallier scores, no significant differences were observed between the retear and no-retear groups (Table 4). When fatty degeneration is observed on MRI, muscle flexibility and cuff mobility are often reduced preoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…Audenaert et al [29] reported that conventional patch grafts that attach the graft with the medial torn tendon stump and the lateral part with greater tuberosity did not show improvement in AHD and that the prevention of humeral head elevation seems difficult using patch grafts. In contrast, in SCR, Mihata et al [5] and Lim et al [24] reported that AHD was significantly improved, and this study (Table 2) also showed improvement in AHD both preoperatively and postoperatively. However, in the retear group, no change in AHD was observed, indicating that the humeral head may be elevated, thereby leading to a decrease in clinical outcomes.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…I n their review, "Superior Capsule Reconstruction for Irreparable Rotator Cuff Tears: A Systematic Review," Zastrow, London, Parsons, and Cagle acknowledge that autograft of fascia lata [1][2][3][4][5][6][7][8][9][10] and acellular dermal allografts 2,[11][12][13][14][15][16] are the materials used most often in superior capsule reconstruction (SCR) for irreparable rotator cuff tears. Importantly, however, they also mention several alternative graft materials for reconstructive surgery.…”
Section: See Related Article On Page 2525mentioning
confidence: 99%
“…His ingenious solution was the SCR, which was a minimally invasive, joint-preserving option that the rest of the world would soon adopt as a legitimate alternative to the RSA and tendon transfers. [3][4][5][6][7][8] To further complicate the issue, stringent regulation and lack of tissue banks limit the availability of allograft tissue in Japan. To meet this challenge, Mihata used fascia lata autograft to reconstruct the superior capsule.…”
Section: See Related Article On Page 579mentioning
confidence: 99%